Posterior capsule opacification and neovascularization treated with intravitreal bevacizumab and Nd:YAG capsulotomy - Grimelda Yuriana Sánchez-Castro (Dove Medical Press, 2008)
Grimelda Yuriana Sánchez-Castro1, Alejandra Hitos-Fájer1, Erick Mendoza-Schuster1, Raul Velez-Montoya2, Cecilio Francisco Velasco-Barona11Asociación para Evitar la Ceguera en México. Hospital “Dr. Luis Sánchez Bulnes”, México, D.F. Ophthalmology Department – Anterior Segment; 2Asociación para Evitar la Ceguera en México. Hospital “Dr. Luis Sánchez Bulnes”, México, D.F. Ophthalmology Department – Retina departmentAbstract: We reported a 75-year-old diabetic man, who developed opacification and neovascularization of the posterior capsule after extracapsular cataract extraction and posterior chamber intraocular lens implantation. The patient was treated with two injections of 2.5 mg of intravitreal bevacizumab. The treatment produced an important regression of the posterior capsular new vessels, allowing us to perform a successful Nd:YAG capsulotomy, clearing the visual axis and improving the visualization of the posterior pole. Even though, best corrected visual acuity was 20/200 due to diabetic macular edema.Keywords: posterior capsule opacification, posterior capsule neovascularization, cataract surgery, postoperative complications, intravitreal bevacizumab